2017
DOI: 10.3892/ol.2017.6115
|View full text |Cite
|
Sign up to set email alerts
|

High expression of P21-activated kinase 5 protein is associated with poor survival in gastric cancer

Abstract: Abstract. P21-activated kinase 5 (PAK5), also termed PAK7, is one of the six members of the PAK family of serine/threonine kinases, which are downstream effectors in several cancer signaling pathways. PAK5 promotes neural outgrowth, contributes to microtubule stability and induces resistance to apoptosis. However, the clinical importance of PAK5 in gastric cancer has not been comprehensively investigated. In the present study, PAK5 expression was evaluated in gastric cancer tissue samples. Furthermore, the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Studies indicate that p21‐activated kinase 5 (PAK5), the most recently identified member of the PAK family, plays an indispensable role in regulation of the cytoskeleton, microtubule stability and cell survival . Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers . Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5–early growth response protein 1 (Egr1)–matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that p21‐activated kinase 5 (PAK5), the most recently identified member of the PAK family, plays an indispensable role in regulation of the cytoskeleton, microtubule stability and cell survival . Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers . Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5–early growth response protein 1 (Egr1)–matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Increasing lines of evidence suggest that PAK5 is an oncogenic protein that is commonly overexpressed in many cancer tissues and contributes to the progression of diverse cancers. [7][8][9][10][11] Likewise, in human breast cancer, PAK5 has been shown to activate a PAK5-early growth response protein 1 (Egr1)-matrix metalloproteinase 2 (MMP2) pathway to control cell migration and invasion. 12 PAK5-directed GATA1 phosphorylation has been reported to induce epithelialmesenchymal transition in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although the six PAKs in mammals are divided into two groups, each member in Group 1 (PAK1-3) shares >90% homology in its kinase domain, while Group 2 members (PAK4-6) share 50% homology in the kinase domain, suggesting that there may be some overlapping functions between PAKs ( 25 ). However, PAKs also present significant differences in their tissue distribution and subcellular localization, which may partly explain the organ-specific effects of these molecules ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…PAK7 was originally found in brain in which promotes the formation of filopodia in nerve cells 9 . However, recent studies have found that the expression level of PAK7 significantly increased in colorectal cancer 10 , 11 , ovarian cancer 12 , gastric cancer 13 - 15 , Neuroglioma 16 , 17 , Hepatocellular carcinoma 18 , 19 , Pancreatic cancer 20 , 21 , Osteosarcoma 22 , and breast cancer 23 - 25 , leading to increased proliferation and migration of tumor cells and inhibition of apoptosis. More importantly, PAK7 expression was positively correlated with the malignancy of colorectal cancer and ovarian cancer, suggesting that PAK7 indeed played an important role in tumor progression.…”
Section: Introductionmentioning
confidence: 99%